Rejection of Wife towards Iwadh Khulu': A Maqasid Sharia Perspective - Arfiana, Arfiana; B, M Taufan; Malkan, Malkan (State Islamic University Datokarama Palu, 2023)
Women were perceived as having a nasty and disturbing image in pre-Islamic times. They are considered worthless and subordinated beings whose presence causes many problems. They have no personal independence, their rights can be taken away from them, and their bodies can be trafficked or passed down through the family, which puts them in a precarious situation. Women are considered not worthy of being treated humanely in these circumstances. In Buol Regency, problems have been related to this iwadh khulu'. In this case, the wife did not receive the iwadh khulu' payment that was handed down to her because, during the time of marriage, the wife was treated improperly by her husband, such as not given a living to support her and her children, often being left alone without news, and not infrequently the husband commits domestic violence to the wife. Based on that, the researchers are interested in further researching this issue and have written a thesis entitled